Design and implementation of a hysteresis band current controller three-phase AC chopper system - Catalbas, Nurbanu; Catalbas, Mehmet Cem; Sunter, Sedat (International Journal of Renewable Energy Research, 2020)
In this study, a three-phase alternative current (AC) chopper circuit was designed and simulated using a hysteresis band current controller (HBCC) method. The HBCC method is often preferred in switching control of AC choppers. The AC chopper circuit, which is both simulated and designed in this study, was composed of six IGBTs. The control of the switches in the circuit was provided by the pulse width modulation (PWM) method and this control in the design was realized by a digital signal processor (DSP) microcontroller. The aim of both the simulation and the design was to examine the output harmonics by ensuring the high quality and efficient operation of the AC chopper circuit. Controlled by the PWM method, this simulation was performed using the MATLAB program. The importance of HBCC in the process of reducing the harmonics in the current was shown in real-time. © 2020 Institut za Arhitekturu i Urbanizam Srbije.
Keywords: AC chopper; Adaptive chopper; Current controller; DSP; HBCC; PWM